ANALISIS PELAKSANAAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) MAHASISWI FKM UIN SUMATERA UTARA PADA MASA NEW NORMAL TAHUN 2023 - Ayu Carolina; Putra Apriadi Siregar (CV. ADIBA AISHA AMIRA, 2023)
The New Normal Era itself is a change in behavior to continue carrying out normal activities with the addition of implementing health protocols to prevent transmission of Covid-19. Not only paying attention to health protocols when doing activities outside the home, but every individual must continue to apply Clean and Healthy Behavior (PHBS) at the household. Because by implementing PHBS each individual will create a healthy lifestyle so that the risk of contracting the Covid-19 virus is very small. The purpose of this study aims to find out about how the implementation of Clean and Healthy Behavior (PHBS) is implemented by FKM female students during the new normal period. The research method used is a qualitative study method with descriptive analysis. The research was conducted through in-depth interviews and observations of FKM student informants and housewives. The instrument used is the voice recorder. The results obtained from this study were that the implementation of PHBS by female students in the new normal period was carried out well, the form of implementation was by implementing a healthy lifestyle such as exercising regularly, consuming nutritious food, sufficient rest time, and maintaining personal hygiene. The conclusion is that the implementation of PHBS among female students during the new normal period has been carried out well.